Regulasi Penyelenggaraan Jaminan Produk Halal di Indonesia Perspektif Statute Approach - Muhammad Aziz; Ahmad Rofiq; Abdul Ghofur (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2019)
his research is focused on the regulation of implementing guarantee for halal products in Indonesia and crucial issues related to them. This research is normative juridical research using a statute approach. The conclusions of this study include; first, there are several crucial issues and topics relating to the implementation of guarantee of halal products in Indonesia, namely halal certification, mandatory and voluntary in halal certification, criminal provisions, and halal product guarantee management institutions. Second, the regulation of halal product guarantees when viewed from the Statute Approach can be analyzed using three legal principles: (1) lex superior derogat legi inferiori concludes that all rules for guaranteeing lower halal products are replaced by the higher ones; (2) lex specialis derogat legi generali confirms that the JPH Law is a specific regulation that regulates the guarantee of halal products; and (3) lex posterior derogat legi priori requires that the rules for guaranteeing halal products as contained in the JPH Law replace the guarantee rules for halal products that existed in the previous period.